Olfactory and Gustatory Functions after Anterior Palatoplasty in Patients with Primary Snoring. (29th March 2016) - Saglam, Omer; Altundag, Aytug; Cayonu, Melih; Salihoglu, Murat; Azizli, Elad; Dursun, Engin; Cetin, Bilal
Abstract : Objective: In this study, we investigated the chemical senses (namely, olfaction), the 4 basic tastes, and umami taste in patients who underwent anterior palatoplasty (AP) for primary snoring. Study Design: Prospective clinical study. Setting: Multicenter, tertiary care hospitals. Subjects and Methods: The age range of the 28 participants was 22 to 47 years, and all had been diagnosed with primary snoring by polysomnography. Orthonasal and retronasal olfactory testing was performed using the respective "Sniffin' Sticks." Tests for the 4 basic tastes (sweet, sour, salty, and bitter) and umami were performed before and 6 months after AP. Results: The changes between the preoperative and postoperative results for the 4 basic tastes, which were applied to the anterior tongue region, were not significant. Retronasal olfactory function improved significantly 6 months after AP ( P =. 007). After AP, umami scores for the soft palate but not those of the anterior and posterior tongue decreased significantly ( P =. 001). Conclusion: Patients scheduled for AP should be properly informed about potential postoperative taste and flavor changes. They should also be warned of a possible loss of appetite due to a postoperative decrease in the umami taste sensation of the soft palate.